A NEW PARENTING IN A CHANGING WORLD 'SHARENTING' - Türker, Meltem; Bahçeci, Ferhat (Stratejik Sosyal ve Kültürel Araştırma Derneği, 2025)
Abstract Social media offers individuals the opportunity to create a digital identity as well as their current identity. However, nowadays, this digital identity is usually not produced by children, but by parents. Every post about children on social media makes children open to digital risks. Reflecting parental identity through the child can bring along various ethical problems. As a matter of fact, in the literature, these posts made by parents about their children on social media are called "sharenting" moreover, a growing body of research has been carried out on this topic in recent years. This study aims to clarify the concept of sharenting, which is the social media posts of parents for their children, to identify the causes behind this behavior, to express the problems that may arise from sharenting and to provide information about legal regulations and sanctions related to sharenting. It is thought that awareness can be raised by examining the sharenting behavior in which parents play a role. Sharenting, which is a new concept in both national and international literature, is aimed to present a conceptual integrity by addressing it with different dimensions in this study. In this context, it is predicted that the analyzes will make a reference contribution to many stakeholders such as researchers, parents and educators who want to learn about the subject. Key words: digital parent, sharenting, parental attitude, attitude.

Özet Sosyal medya, kişilere var olan kimliklerinin yanı sıra dijital bir kimlik oluşturma imkanı da sağlamaktadır. Ancak günümüzde bu dijital kimlik genellikle çocuklar tarafından değil, ebeveynler tarafından oluşturulmaktadır. Sosyal medyada çocuklar hakkında yapılan her paylaşım, çocukları dijital risklerle karşı karşıya bırakmaktadır. Ebeveyn kimliğinin çocuklar aracılığıyla yansıtılması, etik açıdan çeşitli sorunları gündeme getirebilir. Nitekim literatürde, ebeveynlerin çocukları hakkında sosyal medyada yaptıkları bu paylaşımlar 'sharenting' olarak tanımlanmakta ve bu konuda son yıllarda giderek artan sayıda araştırma yapılmaktadır. Bu çalışmanın amacı, ebeveynlerin çocuklarıyla ilgili sosyal medya paylaşımları olan sharenting kavramını açıklamak, bu davranışın nedenlerini ortaya koymak, sharenting’in yol açabileceği sorunları tartışmak ve sharenting ile ilgili yasal düzenlemeler ve yaptırımlar hakkında bilgi sunmaktır. Ebeveynlerin gerçekleştirdiği sharenting davranışını inceleyerek bu konuda farkındalık yaratılabileceği düşünülmektedir. Hem ulusal hem de uluslararası literatürde yeni bir kavram olan sharenting, bu çalışmada farklı yönleriyle ele alınarak kavramsal bir bütünlük oluşturulması hedeflenmektedir. Bu doğrultuda yapılacak analizlerin, konu hakkında bilgi edinmek isteyen araştırmacılar, ebeveynler ve eğitimciler gibi birçok paydaşa kaynak niteliğinde bir katkı sağlayacağı öngörülmektedir.
Değişen Dünyada Yeni Bir Ebeveynlik ‘Sharenting’
Keywords: Communication and Media Studies (Other); İletişim ve Medya Çalışmaları (Diğer)